The Roadmap to Mainframe Modernization: Bridging Legacy Systems with the Cloud - Narasimha Rao Vanaparthi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The modernization of mainframe systems represents a critical inflection point for financial institutions seeking to remain competitive in an increasingly digital marketplace. This comprehensive technical article presents a strategic framework for transitioning from legacy mainframe infrastructure to cloud-native solutions, emphasizing risk mitigation and business continuity. Through detailed analysis of implementation methodologies, data migration strategies, and security architectures, financial organizations can leverage modern cloud platforms while preserving the reliability and security inherent in traditional mainframe systems. The article examines real-world case studies and empirical evidence demonstrating how institutions have successfully navigated common challenges, including regulatory compliance, system integration, and operational transformation. Special attention is given to the practical aspects of maintaining business operations during migration, implementing robust security controls, and establishing scalable cloud operations models. By providing a comprehensive roadmap encompassing technical and organizational considerations, this article serves as an essential resource for technology leaders and architects tasked with modernizing mission-critical mainframe systems while ensuring minimal disruption to core business functions.